Adoption Agrafa, Parts “Unwritten” About Cold War Adoptions from Greece - Gonda A. H. Van Steen (Genealogy)
This preliminary empirical study delves into the “agrafa”, the “unwritten” or “uncharted” parts of a Greek adoption phenomenon and Greek–American relations that may, however, still be accessed via archival investigations, mixed research methods, and efforts to hone life writing skills. At stake is the case of the post-WWII adoptions of some 4000 Greek children who were sent to the United States between the years 1950 and 1975. This study asks how the related negotiations were transacted, especially in the early years of the intercountry adoption phenomenon. It challenges the researcher today to create a life writing narrative out of scant snippets and dense allusions and to disclose the dynamics of overlooked interactions, such as the consumerist and occasionally racist attitudes of some, though certainly not all, prospective adoptive parents. Thus, this article highlights formerly dismissed interactions, not necessarily numerically representative interactions, given that the window of opportunity has passed to interview adoptive parents of Greek children who pursued these foreign adoptions in the 1950s–1960s and to quantify their actions and reactions more systematically. Many of the adoptive parents of the 1950s–1960s, however, left their impressions, demands, and frustrations in writing. Those writings have yet to be studied, and their more deliberate, explicit language must be acknowledged, even amid generally more positive depictions of postwar intercountry adoption. I show that the victorious post-WWII era saw a sense of American entitlement emerge among the prospective adoptive parents that has since been whitewashed. Waiving the banner of altruism or humanitarianism (as a couple or as a superpower, respectively), some adoptive parents embarked on adoptions from Greece from a position of cultural as well as political and economic superiority. Their expectation was that the “destitute” partner should comply, that the Greeks themselves should not “talk back” when “poor orphans” were about to be “saved” from “illegitimacy” and lack of prospects.